(untitled) (Journal of Plant Disease Sciences, 2018)
Inoculum densities and isolates of F. oxysporum f. sp. ciceri (weak or highly pathogenic) significantly influenced quantitative development of Fusarium wilt in three chickpea cultivars, with increase in final population over initial. The inoculums levels of 50 and 100 g per kg soil of WPI leads to 7.0 and 13.3 per cent wilt incidence in JG-62. But with increase in inoculums levels of HPI cultivar JG-62 showed progressive increase in wilt incidence and attained 100 per cent wilting at 25, 50 and 100 g/kg soil inoculums levels. The rate of multiplication of cfu in cv. JG-62 is more, ranged from 12.19 to 1.89 per 50 mg soil than AKG-96 (moderately susceptible) and SAKI-9516 (resistant). Evaluation of 65 genotypes against Fusarium wilt under pot and water culture showed that, only three (PG-05112, AKG-84 and AKG-88) and two genotypes viz., PG-05112 and AKG-84 were found disease free under pot culture and water culture respectively. However, 15 and 17 chickpea genotypes showed a highly susceptible reaction in pot culture and water culture.